Resection of the aorta and infrarenal cava due to metastatic retroperitoneal tumor of germinal origin - Pereyra, Jorge; Jubin, Juan; Arroyo, Carlos (Cirugía del Uruguay, 2003)
A 24 year old patient caried a germinal tumor which had originated in the retroperitoneal region. Treatment with various fines of chemotherapy was followed by a "desperate" retroperitoneal lymphadenectomy involving resection of infra-renal vena cava and aorta and subsequent reconstruction of both vessels.